Activation of CO2 and CH4 on MgO surfaces: mechanistic insights from first-principles theory. Issue 3 (4th January 2022) - Manae, Meghna A.; Dheer, Lakshay; Rai, Sandhya; Shetty, Sharan; Waghmare, Umesh V.
Abstract : Using DFT calculations, we propose O-terminated (111) surface of MgO as a suitable catalyst for Oxidative Coupling of Methane as it cleaves 3 C—H bonds in CH4, and interacts weakly with CO2, a byproduct, thus avoiding poisoning via MgCO3  formation. Abstract : One of the most challenging topics in heterogeneous catalysis is conversion of CH4 to higher hydrocarbons. Direct conversion of CH4 to ethylene can be achieved via the oxidative coupling of methane (OCM) reaction. Despite studies which have shown MgO to activate CH4 and initiate the OCM reaction, its large-scale applications face a significant impediment due to formation of a byproduct, CO2, and poisoning of the catalyst due to carbonate formation. In the present work, we address two aspects of the OCM reaction on MgO surfaces: carbonate formation on the surface of the catalyst, and (dissociative) adsorption of CH4 . We use first-principles density functional theoretical calculations to determine the energetics and underlying mechanisms of interaction of CO2 and CH4 with various surfaces of MgO: (100), (110), and (111) (both Mg- and O-terminations), and the seldom studied, hydroxylated (111) MgO surface with O-termination. We find that the strength of the interaction of CO2 with MgO surfaces depends on several factors: their surface energies, coordination number of surface O atoms, and ability to donate electrons. However, the O-terminated (111) surface of MgO bucks all aforementioned factors, with only oxygen richness affecting its reactivity towards CO2 . The interaction of CH4 with MgO surfaces depends primarily on the coordination number of the surface O atoms and the orientation of the CH4 molecule with respect to the surface. Finally, we provide insights into (a) formation of surface carbonates, which is relevant to CO2 capture and conversion, and (b) C–H bond activation on MgO surfaces, which is crucial for direct conversion of CH4 to value-added chemicals.